Earnings Management and Firms’ Behavior During the Global Financial Crisis : Comparative Analysis of Selected Common Law and Civil Law Countries - Svitlík, Jan, 1987- (2018)
The dissertation deals with firms’ behavior during the global financial crisis (2008-2009) in the UK, the common law representative, Germany and the Czech Republic, the civil law representatives. Period of 2006-2011 is investigated. Earnings management of companies is primary focus of the research; nevertheless, multiple analyses regarding profitability, leverage and taxation characteristics of companies are undertaken. Theoretical part of the dissertation covers history and characteristics of legal families, genesis and development of the global financial crisis, and previous research on earnings management. Broad datasets from Amadeus database are used under empirical part of the dissertation. Profitability analyses prove the severest impact of the crisis on European non-financial companies in 2008 and 2009. Both lightly and highly leveraged companies indicate lower profitability than moderately leveraged companies which is in line with capital structure theories. Leverage analyses show gradual decrease in leverage ratio within non-financial sector, more specifically, individual firm-size categories exhibit parallel declining trend in the UK, converging declining trend in Germany, and diverging declining trend in the Czech Republic. Taxation analyses suggest high influence of governments’ tax relief programs in the crisis period. Earnings management analyses detect the highest level of earnings management in the Czech Republic while the lowest in the UK. Czech companies engaged in upward earnings management in 2009 indicating the earnings-smoothing strategy during the crisis period. By contrast, downward earnings management is detected in the UK and Germany in 2008 and 2009 suggesting the big-bath strategy. In general, medium-sized companies are more likely engaged in downward earnings management than upward earnings management.